2021
DOI: 10.1093/nar/gkab854
|View full text |Cite
|
Sign up to set email alerts
|

eIF3j facilitates loading of release factors into the ribosome

Abstract: eIF3j is one of the eukaryotic translation factors originally reported as the labile subunit of the eukaryotic translation initiation factor eIF3. The yeast homolog of this protein, Hcr1, has been implicated in stringent AUG recognition as well as in controlling translation termination and stop codon readthrough. Using a reconstituted mammalian in vitro translation system, we showed that the human protein eIF3j is also important for translation termination. We showed that eIF3j stimulates peptidyl-tRNA hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(75 reference statements)
1
7
0
Order By: Relevance
“…4B). Western blotting showed that under low-salt (LS) conditions, significant amounts of eIF3 remained in the preTC(LS), which was also shown in our previous study (45). After high-salt (HS) centrifugation, we observed a significant decrease of eIF3 in the preTC(HS).…”
Section: Influence Of Translation Initiation Factors On the Stop Codo...supporting
confidence: 87%
See 4 more Smart Citations
“…4B). Western blotting showed that under low-salt (LS) conditions, significant amounts of eIF3 remained in the preTC(LS), which was also shown in our previous study (45). After high-salt (HS) centrifugation, we observed a significant decrease of eIF3 in the preTC(HS).…”
Section: Influence Of Translation Initiation Factors On the Stop Codo...supporting
confidence: 87%
“…The 3ʹ context UGU GUG was chosen as the Standard. This context has been used in all our previous studies in the reconstituted mammalian translation system (3,39,(41)(42)(43)(44)(45)(46)(47). The frequencies of triplets from this sequence in the human genome calculated earlier (1-1.8%) were close to that for random triplet NNN 1/64 = 1.56% (39).…”
Section: Factors Influencing Stop Codon Readthrough Efficiencymentioning
confidence: 69%
See 3 more Smart Citations